The Influence of Odors on Time Perception - Millot, Jean-Louis; Laurent, Lucie; Casini, Laurence (Frontiers in Psychology, 2016)
The effect of an olfactory stimulation on the perception of time was investigated through two different experiments based on temporal bisection tasks. In experiment 1, the durations to be classified as either short or long were centered on 400 ms while in Experiment 2 there were centered on 2000 ms. The participants were different in the two experiments (36 subjects in each one). In each experiment, half of the subjects learnt the anchor durations when smelling an unpleasant odor (decanoic acid) and the other half when smelling no odor. After the learning phase, both groups were tested with and without odor. The results showed opposite effects depending on the duration range. The subjects underestimated the time in the presence of the unpleasant odor in the short duration range while they overestimated it in the long duration range. The results have been discussed in the framework of the pacemaker-counter clock model and a potential emotional effect induced by the odor on the subjective time perception has also been considered.